MODEL DIALOG IMAJINER ENTAS-ENTAS UNTUK MENGKOMUNIKASIKAN KRISTUS KEPADA MASYARAKAT TENGGER - Daniel Fajar Panuntun; Jimmi Pindan Pute; Lisdayanti Anita Mangalik (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2020)
Indonesia has a diversity of cultures, and each culture has its characteristics and these cultures cannot be eliminated. Simultaneously the Tengger Tribe has the privilege of entas culture, where this culture is a ritual that is held to commemorate the death and to ask the Supreme Court so that the spirits who have died get a good place. Based on these cultural features, Christianity must have a mission to communicate Christ to the Tengger Tribe. The mission can be carried out using apologetic dialogue. The apologetic dialogue is based on the conversational theory of evangelism from Geisler. The apologetic dialogue also refers to the God and Culture theory of Richard Neighbor. The apologetic dialogues are arranged in an imaginary dialogue that can be developed and practised by every believer. The purpose of this paper is, first, to know the biblical apologetic dialogue model. Second, knowing the context of entas- ter in the Tengger society. Third, obtain an imaginary Dialogue Model for communicating Christ to the Tengger community. Based on this research, the method used by the author is literature study and Bible study. The apologetic dialogue produced is expected to be a pre-evangelism for the Tengger society.